Suppression of the breakthrough of human immunodeficiency virus type 1 (HIV-1) in cell culture by thiocarboxanilide derivatives when used individually or in combination with other HIV-1-specific inhibitors (i.e., TSAO derivatives). - Balzarini, J (1995)
Five structurally related thiophene and furane analogues of the oxathiin carboxanilide derivative NSC 615985 (UC84) (designated UC10, UC68, UC81, UC42, and UC16) were identified as potent inhibitors of HIV-1 replication in cell culture and HIV-1 reverse transcriptase activity. These compounds were markedly active against a series of mutant HIV-1 strains, containing the Leu-100-->Ile, Val-106-->Ala, Glu-138-->Lys, or Tyr-181-->Cys mutations in their reverse transcriptase. However, the thiocarboxanilide derivatives selected for mutations at amino acid positions 100 (Leu-->Ile), 101 (Lys-->Ile/Glu), 103 (Lys-->Thr/Asp) and 141 (Gly-->Glu) in the HIV-1 reverse transcriptase. The compounds completely suppressed HIV-1 replication and prevented the emergence of resistant virus strains when used at 1.3-6.6 microM--that is, 10- to 25-fold lower than the concentration required for nevirapine and bis(heteroaryl)piperazine (BHAP) U90152 to do so. If UC42 was combined with the [2',5'-bis-O-(tert-butyldimethylsilyl)-3'-spiro-5"-(4"-amino-1",2"- oxathiole-2",2"-dioxide)]-beta-D-pentofuranosyl (TSAO) derivative of N3-methylthymine (TSAO-m3T), virus breakthrough could be prevented for a much longer time, and at much lower concentrations, than if the compounds were used individually. Virus breakthrough could be suppressed for even longer, and at lower drug concentrations, if BHAP was added to the combination of UC42 with TSAO-m3T, which points to the feasibility of two- or three-drug combinations in preventing virus breakthrough and resistance development.